Subject Files
The series contains subject files created for research purposes by the RFE Polish Unit. It is arranged alphabetically and based mostly on xerox copies of clippings from Polish independent publications, but also includes RFE-produced materials (A-wires, B-wires, situation reports, background reports) and clippings from the foreign press, as well as photos and leaflets. The series documents a variety of aspects of political, social and cultural life in Poland and other countries as well. The topics covered include: state-opposition relations, political activities of the Solidarity movement and independent political groups; political trials and cases of state repression (with individual files on the persecuted); the independent press and cultural life, the Catholic Church, the Chernobyl disaster; economic reform; human rights and the Helsinki Committee in Poland; the youth movement; the situation in different countries of the Communist bloc; the 1989 Round Table and elections in Poland. Accruals not expected